Detection of a Rare Blood Group ‘Bombay (Oh) Phenotype’ – A case report from Asgar Ali Hospital (Pulse, 2024)
Bombay blood group is a rare blood type. It was first discovered in Bombay (Mumbai) in India. At the time of blood grouping, this blood group mimics O blood group due to the absence of H antigen, but it shows incompatibility with O group blood during cross-matching. Serum grouping or reverse grouping is essential for confirmation of the diagnosis. Patients carrying this blood group can receive blood only from a person with this blood group. Here, we present a case of Bombay phenotype in a patient with subarachnoid hemorrhage.Pulse Vol.15, 2023 P: 51-53